On the immature stages of the crazy ant Paratrechina longicornis (Latreille 1802) (Hymenoptera: Formicidae) - Fox, Eduardo Gonçalves Paterson; Solis, Daniel Russ; de Jesus, Carlos Massuretti; Bueno, Odair Correa; Yabuki, Antonio Teniyoshi; Rossi, Mônica Lanzoni (Zootaxa, 2007)
The ant Paratrechina longicornis is a cosmopolitan ant species that has been accidentally spread by commerce around the world, and now is a pest of houses and hospitals. The morphology of its larval stages has been previously described without knowledge of the number of instars. The present study revisits the original description of P. longicornis larvae by adding differences observed among the three larval instars. Compared to other Paratrechina species studied so far, P. longicornis presents smaller larvae, less evident variation in mandible morphology, and clear variation in the morphology of head hairs between the analysed specimens of the second and third instar larvae. Ultrastructural images of the eggs, larval spiracle ornamentation, and pupae are also presented for the first time.